ASSESSMENT OF THE QUALITATIVE INFLUENCE OF FACTORS ON THE SENSITIVITY OF MOISTURE SENSITIVE MDS CAPACITOR BASED ON AMORPHOUS SILICON(IV) OXIDE - KRYLIK, LYUDMILA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The work uses multifactorial dispersion analysis to assess the qualitative influence of factors: the thickness of the moisture-sensitive amorphous silicon(IV) oxide layer; the diameter of the pores of moisture-sensitive amorphous silicon(IV) oxide, as well as their combined effect on the sensitivity of the moisture-sensitive MDS (metal-dielectric-semiconductor) capacitor based on amorphous silicon(IV) oxide. The experimental sample was a moisture-sensitive MDS capacitor, which is made on an n-type silicon plate with crystallographic orientation <100>, on the lower side of which a highly doped n+ layer is created using high-temperature diffusion. Such a plate serves as the lower electrode of the structure. A SiO2 film, which is the dielectric of this structure, is created on the planar side of the plate using the process of thermal oxidation. A porous SiO2 film with a thickness of 1 μm is created on the surface of thermally oxidized SiO2 by low-temperature oxidation in moist oxygen. A mesh aluminum electrode serves as the upper electrode of the structure. To create an ohmic contact, a thin layer of aluminum is sprayed on the reverse side of the plate. A multivariate plan was developed for two qualitative factors. With the use of multivariate dispersion analysis, it was proved that the response of the model, namely, the sensitivity of the moisture-sensitive MDS capacitor based on amorphous silicon(IV) oxide, is affected by the factor - the diameter of the pores of the moisture-sensitive amorphous silicon(IV) oxide. In this case, the value of Fisher’s criterion observed in the experiment significantly exceeds the critical value of Fisher’s criterion, namely, F>Fkr (16.44>4.75). The difference in the response values of the model is related only to the change in the value of the factor. The influence of such factors is the thickness of the layer of moisture-sensitive amorphous silicon(IV) oxide, the combined effect: the thickness of the layer of moisture-sensitive amorphous silicon(IV) oxide + the diameter of the pores of moisture-sensitive amorphous silicon(IV) oxide is insignificant, that is, the difference in the response values of the model is due only to the random nature (F < Fkr). On the basis of dispersion analysis, it was proved that the sensitivity of the moisture-sensitive MDS capacitor based on amorphous silicon(IV) oxide is affected only by the size of the pores of amorphous silicon(IV) oxide.